Contrast of Backscattered Electron SEM Images of Nanoparticles on Substrates with Complex Structure. (6th April 2017) - Kowoll, Thomas; Müller, Erich; Fritsch-Decker, Susanne; Hettler, Simon; Störmer, Heike; Weiss, Carsten; Gerthsen, Dagmar
Abstract : This study is concerned with backscattered electron scanning electron microscopy (BSE SEM) contrast of complex nanoscaled samples which consist of SiO2 nanoparticles (NPs) deposited on indium-tin-oxide covered bulk SiO2 and glassy carbon substrates. BSE SEM contrast of NPs is studied as function of the primary electron energy and working distance. Contrast inversions are observed which prevent intuitive interpretation of NP contrast in terms of material contrast. Experimental data is quantitatively compared with Monte-Carlo- (MC-) simulations. Quantitative agreement between experimental data and MC-simulations is obtained if the transmission characteristics of the annular semiconductor detector are taken into account. MC-simulations facilitate the understanding of NP contrast inversions and are helpful to derive conditions for optimum material and topography contrast.